KEDUDUKAN FIDUSIA SEBAGAI LEMBAGA JAMINAN DALAM SISTEM PEREKONOMIAN - Hartiana, Alberta; Dharmakusuma, A. A. Gde Agung (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
Employment agreement between employer party and employee party is made byusing fixed agreement, so within the process of making agreement is not through precontractsteps as it is normally initiated with negotiation process between employee partyand employer party and also this agreement is made under hand. Although employmentagreement is made in term of fixed agreement and under hand, but this agreement keeps onthe effort to refer to regulation listed in Article 1320 Civil Act and Article 52 point 1 ofIndonesian Republic Regulation no. 13 of 2003 as it is the legal main condition for anagreement and also as the basic law of employment agreement.The legal consequence of employment agreement which is made between employerparty and employee party that the sanction assigned to employees who violate theregulation agreed in this employment agreement, namely: If employer or employeeterminate employment agreement within certain period prior ended, so the party whoterminates this employment agreement must pay compensation to other party at the restsalary of the worker until the period or the worker should finish his contract period, excepttermination of employment agreement die to serous force/fault from employee. Any dispute taken place as consequence of this employment agreement should be settled by both partiesthrough Registration Office of District Court Denpasar.
Keywords: Employment Agreement, Employer Party, Employee Party, Economic System